Analysis of Complement C3 Gene Reveals Susceptibility to Severe Preeclampsia - Lokki, A. Inkeri; Kaartokallio, Tea; Holmberg, Ville; Onkamo, Päivi; Koskinen, Lotta L. E.; Saavalainen, Päivi; Heinonen, Seppo; Kajantie, Eero; Kere, Juha; Kivinen, Katja; Pouta, Anneli; Villa, Pia M.; et al. (Frontiers in Immunology, 2017)
Preeclampsia is a common vascular disease of pregnancy with genetic predisposition. Dysregulation of the complement system has been implicated, but molecular mechanisms are incompletely understood. In this study, we determined the potential linkage of severe preeclampsia to the most central complement gene, C3. Three cohorts of Finnish patients and controls were recruited for a genetic case-control study. Participants were genotyped using Sequenom genotyping and Sanger sequencing. Initially, we studied 259 Finnish patients with severe preeclampsia and 426 controls from the Southern Finland preeclampsia and the Finnish population based preeclampsia cohorts. We used a custom-made single nucleotide polymorphism (SNP) genotyping assay consisting of 98 SNPs in 18 genes that encode components of the complement system. Following the primary screening, C3 was selected as the candidate gene and consequently Sanger sequenced. Fourteen SNPs from C3 were also genotyped by a Sequenom panel in 960 patients with severe preeclampsia and 705 controls, including already sequenced individuals. Three of the 43 SNPs observed within C3 were associated with severe preeclampsia: rs2287845 (p=0.038, OR=1.158), rs366510 (p=0.039, OR=1.158), and rs2287848 (p=0.041, OR=1.155). We also discovered 16 SNP haplotypes with extreme linkage disequilibrium in the middle of the gene with a protective (p=0.044, OR=0.628) or a predisposing (p=0.011, OR=2.110) effect to severe preeclampsia depending on the allele combination. Genetic variants associated with preeclampsia are located in key domains of C3 and could thereby influence the function of C3. This is, as far as we are aware, the first candidate gene in the complement system with an association to a clinically relevant preeclampsia subphenotype, severe preeclampsia. The result highlights a potential role for the complement system in the pathogenesis of preeclampsia and may help in defining prognostic and therapeutic subgroups of preeclamptic women.